Investigating the link between the L2 motivational self system and learning strategy use - Batsari, Sophia; Sougari, Areti-Maria (American Journal of Education and Learning, 2025)
The purpose of this paper is to explore the relationship between motivation, learning strategy use, and English proficiency level in the context of learning English as a foreign language in primary and secondary education in Greece. The L2 Motivational Self System (L2MSS) and the Strategy Inventory for Language Learning (SILL) provided the theoretical frameworks for the study to investigate links between the components of each model. The sample comprised 380 primary and 482 lower secondary learners in Greek state schools who were selected by the proportionate stratified random sampling method in two stages. Quantitative data was collected by means of a motivation and learning strategy questionnaire survey and the Quick Placement Test to measure learners’ English proficiency. The results revealed higher motivation and learning strategy scores for primary school learners. At the same time, English proficiency level correlated highly with motivation components for both levels of education, while strong correlations were reported between particular motivation and learning strategy components for primary as well as secondary school learners. In the light of the findings, the advancement of positive learning environments where learners are engaged in practical learning outcomes calls for policy implementation that should be promoted by curriculum designers and educators.